(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The present study investigates the psychological factors influencing trainee teachers and teacher-educators in teacher training institutions of Nadia District, West Bengal, focusing on anxiety, job satisfaction, and future career perspective. The study adopted a descriptive-cum-exploratory research design with a total sample of 300 participants, including 250 trainee teachers and 50 teacher-educators across five teacher training colleges. The research examines the levels and distribution of anxiety and job satisfaction, compares these variables across key categorical groups (gender, role, institution type, and locality), and explores their relationships with future career perspective, controlling for demographic factors. Findings reveal that moderate levels of anxiety are prevalent among trainee teachers, while teacher-educators report comparatively higher job satisfaction (Sharma & Singh, 2019; Patra & Roy, 2021). Gender, role, and institution type significantly influence anxiety and job satisfaction scores, whereas locality and TTC affiliation show mixed effects (Das & Ghosh, 2017; Chatterjee, 2018). Future career perspective is positively associated with job satisfaction and negatively related to anxiety, highlighting the interdependence of psychological well-being and professional outlook (Gupta & Kaur, 2020; Collie, Shapka, & Perry, 2012). The study underscores the importance of psychological support, career counseling, and institutional interventions to enhance the professional preparedness and well-being of future educators in West Bengal.